Continuous-Flow Analysis of δ17O, δ18O, and δD of H2O on an Ice Core from the South Pole - Steig, Eric J.; Jones, Tyler R.; Schauer, Andrew J.; Kahle, Emma C.; Morris, Valerie A.; Vaughn, Bruce H.; Davidge, Lindsey; White, James W.C. (Frontiers in Earth Science, 2021)
The δD and δ18O values of water are key measurements in polar ice-core research, owing to their strong and well-understood relationship with local temperature. Deuterium excess, d, the deviation from the average linear relationship between δD and δ18O, is also commonly used to provide information about the oceanic moisture sources where polar precipitation originates. Measurements of δ17O and “17O excess” (Δ17O) are also of interest because of their potential to provide information complementary to d. Such measurements are challenging because of the greater precision required, particularly for Δ17O. Here, high-precision measurements are reported for δ17O, δ18O, and δD on a new ice core from the South Pole, using a continuous-flow measurement system coupled to two cavity ring-down laser spectroscopy instruments. Replicate measurements show that at 0.5 cm resolution, external precision is ∼0.2‰ for δ17O and δ18O, and ∼1‰ for δD. For Δ17O, achieving external precision of <0.01‰ requires depth averages of ∼50 cm. The resulting ∼54,000-year record of the complete oxygen and hydrogen isotope ratios from the South Pole ice core is discussed. The time series of Δ17O variations from the South Pole shows significant millennial-scale variability, and is correlated with the logarithmic formulation of deuterium excess (dln), but not the traditional linear formulation (d).